2005
DOI: 10.1007/s10651-005-1518-3
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Level Spatial Analysis of the Relationship Between Alcohol Outlet Density and Criminal Violence

Abstract: Misuse of alcohol is a significant public health problem, potentially resulting in unintentional injuries, motor vehicle crashes, drownings, and, perhaps of greatest concern, serious acts of violence, including assaults, rapes, suicides, and homicides. Although previous research establishes a link between alcohol consumption increased levels of violence, studies relating the density of alcohol outlets (e.g., restaurants, bars, liquor stores) and the likelihood of violent crime have been less common. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 26 publications
5
85
0
3
Order By: Relevance
“…These findings are consistent with a body of research that has shown that the presence and density of alcohol outlets are associated with violent crime in cities with a population 200,000 or greater in the US. 9,10,14,[27][28][29][30][31][32][33] For example, a study in Washington DC found that community-level liquor outlet density was significantly associated with violent crimes, independent of other neighborhood factors including violent crime, and the prevalence of weapons and illicit drugs. 21 Another study in Los Angeles, found that the total liquor outlet density was positively related to the assault rate (one type of violent crime) over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a body of research that has shown that the presence and density of alcohol outlets are associated with violent crime in cities with a population 200,000 or greater in the US. 9,10,14,[27][28][29][30][31][32][33] For example, a study in Washington DC found that community-level liquor outlet density was significantly associated with violent crimes, independent of other neighborhood factors including violent crime, and the prevalence of weapons and illicit drugs. 21 Another study in Los Angeles, found that the total liquor outlet density was positively related to the assault rate (one type of violent crime) over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…However, police data is often used in these kinds of analyses (e.g. Miles-Doan and Kelly, 1997; Bartolo, 2001;Britt et al, 2005;Gorman et al, 2005), and the use of a range of control variables related to police reporting rates (e.g. socioeconomic disadvantage) will ameliorate this bias somewhat.…”
Section: Methodsmentioning
confidence: 99%
“…This was extended by Besag et al (1991) to separate spatial variability from random heterogeneity in regional disease maps. Britt et al (2005) and Zhu et al (2006) examined the relationship between alcohol outlet density and violence in different areas using hierarchical Bayesian spatial models. In this paper, we add a dual temporal changepoint dimension to the modeling in order to analyze trends in assaultive violence in Los Angeles at the census tract-level.…”
Section: Introductionmentioning
confidence: 99%